English as a Second Language learners and teachers' conceptions of language assessment - Nimehchisalem, Vahid; Foo, Edmund Sze Kai; Nowrouzi, Sara (Asia T E F L,Teachers of English as a Foreign Language, 2019)
Currently, ministries of education in some developing countries, such as Malaysia and Iran, are planning to transform their often-centralized tests to school-based assessment. This is good news but before making any changes, one must ask if stakeholders in such communities are ready for any changes. The objective of this study was to compare the conceptions of assessments of English as a Second Language (ESL) teachers and students. Qualitative methods were used to collect the data using a questionnaire with open-ended tasks developed, validated, piloted and refined by the researchers. The data were analyzed through inductive and deductive thematic analysis approaches. The results also indicated that both students and teachers frequently view assessment as tests and scores, and yet there were differences between their conceptions. For example, while teachers were more concerned with standards and validity, themes such as cheating emerged from students' data. Assessment was also found to be stimulator of both adaptive behavior (such as an instrumental motivator) and maladaptive behavior (such as cheating) among students. These results offer remarkable implications for language learning, teaching, and testing for education policy-makers in developing countries.